EVALUATION OF THE PATHOMORPHOLOGY OF REGENERATION IN DIABETIC FOOT SYNDROME AND DETERMINATION OF ITS DEPENDENCE ON BIOCHEMICAL PROCESSES - Ergashev U.Y.; Ernazarov Kh.I.; Abdusalomov B.A.; Minavarkhojayev R.R.; Ortiqboyev F.D.; Malikov N.M. (Scholar Express Journals, 2023)
The aim of the study was tolearn of the effect of the new drug "Reomannisol" on wound healing, taking into account pathomorphological aspects in the complex treatment of experimental diabetic foot syndrome.
Keywords: experimental model of diabetic foot; experimental animals; diabetes mellitus; alloxan